2018
DOI: 10.1111/nph.15406
|View full text |Cite
|
Sign up to set email alerts
|

Homologs of the STYLISH gene family control nectary development in Aquilegia

Abstract: Floral nectaries are an interesting example of a convergent trait in flowering plants, and are associated with the diversification of numerous angiosperm lineages, including the adaptive radiation of the New World Aquilegia species. However, we know very little as to what genes contribute to nectary development and evolution, particularly in noncore eudicot taxa. We analyzed expression patterns and used RNAi-based methods to investigate the functions of homologs from the STYLISH (STY) family in nectar spur dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 40 publications
3
45
0
Order By: Relevance
“…In our study MYB305 , a key transcription factor in eudicot floral nectary function (Liu & Thornburg, ; Liu et al., ; Schmitt et al., ; Wang et al., ), displayed little difference in expression between squash male and female nectaries; however, three transcription factors —SHI‐related sequence 1 , heat stress transcription factor A‐6b, and UNUSUAL FLORAL ORGANS‐like— displayed preferential expression female over male nectaries. Interestingly, SHI‐related sequence 1 is a member of the STYLISH gene family, which control nectary development in Aquilegia (Min, Bunn, & Kramer, ).…”
Section: Discussionsupporting
confidence: 91%
“…In our study MYB305 , a key transcription factor in eudicot floral nectary function (Liu & Thornburg, ; Liu et al., ; Schmitt et al., ; Wang et al., ), displayed little difference in expression between squash male and female nectaries; however, three transcription factors —SHI‐related sequence 1 , heat stress transcription factor A‐6b, and UNUSUAL FLORAL ORGANS‐like— displayed preferential expression female over male nectaries. Interestingly, SHI‐related sequence 1 is a member of the STYLISH gene family, which control nectary development in Aquilegia (Min, Bunn, & Kramer, ).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the diversity, it is widely accepted that the nectary has been one of the most influential key innovations that promoted the diversification of many plant lineages 7,[12][13][14] . Meanwhile, it has been found that, to secrete nectar, nectary cells should be able to synthesize and transport sugar and other necessary components 10,[15][16][17] ; genes regulating the formation and proper functioning of nectaries, such as CRABS CLAW (CRC) of the YABBY family, STYLISH1(STY1), STY2, and LATERAL ROOT PROMORDIUM (LRP) of the STY family, and SWEET9 of the SWEET family, therefore, are indispensable (at least in eudicots) 2,16,[18][19][20] .…”
mentioning
confidence: 99%
“…In our study MYB305, a key transcription factor in eudicot floral nectary function (Liu et al, 2009; Liu and Thornburg, 2012; Wang et al, 2014; Schmitt et al, 2018), displayed little difference in expression between squash male and female nectaries; however, three transcription factors – SHI-related sequence 1, heat stress transcription factor A-6b and UNUSUAL FLORAL ORGANS-like – displayed preferential expression female over male nectaries. Interestingly, SHI-related sequence 1 is a member of the STYLISH gene family, which control nectary development in Aquilegia (Min et al, 2018).…”
Section: Discussionmentioning
confidence: 99%